Evaluating the analytical performance of four new coagulation assays for the measurement of fibrinogen, D‐dimer and thrombin time. (22nd July 2018) - Kitchen, Steve; Geisen, Ulrich; Kappelmayer, Janos; Quehenberger, Peter; Lowe, Anna; Jones, Robert; Miles, Gabrielle; Boehm, Jana G.; Rozsnyai, Gergely
Abstract: Introduction: New laboratory methods to measure haemostatic function require careful assessment before routine use. We evaluated the analytical performance of four new coagulation assays for the measurement of fibrinogen by Clauss assay, prothrombin time‐derived fibrinogen, thrombin time and D‐dimer levels. Methods: The four assays were evaluated on thecobas t 711 andcobas t 511 analysers at four centres in Europe. Analytical performance and method comparisons with other commercially available assays were performed according to Clinical and Laboratory Standards Institute guidelines (EP09‐A3, EP05‐A3) using residual anonymized human sodium citrate (3.2% [0.109M]) plasma samples. Lot‐to‐lot variability and the equivalency of each assay on thecobas t 711 andcobas t 511 analysers were also assessed. Results: Overall, coefficients of variance were ≤4.1% and ≤8.6% for within‐run precision and total reproducibility, respectively. Method comparison experiments showed good or acceptable agreement for each assay compared with their respective comparator method, and equivalency was demonstrated for the twocobas t platforms (Pearson's correlation coefficient ≥0.991). A high level of consistency was observed between lots for all four assays (Pearson's correlation coefficient ≥0.994). Conclusion: This multicentre study demonstrates excellent analytical performance for four new coagulation assays on thecobas t 711 andcobas t 511 analysers.